Factors Affecting Intentions and Behavior of Plagiarism Among Students in Jambi University: Testing the Data Quality for Validity and Reliability - Firman Firman; Yusdi Anra; Robin Pratama; Friscilla Wulan Tersta (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
This study aims to identify the factors that influence students' intention to plagiarize or plagiarize. To model plagiarism intention and behavior among college students, this proposed research refers to Theory Planned Behavior (TPB) by incorporating new variables of moral obligation and past behavior and using ICT literacy as part of perceived behavioral control. With a sample of 511 FKIP UNJA students, this study used a research methodology and model parameter estimation supported by Structural Equation Modeling (SEM). Testing the validity and reliability with the PLS Algorithm stages produces path coefficients (PLS-Algorithm). Based on the output coefficient path indicator which has a loading factor coefficient below 0.708 is dropped from the research model. After dropping indicators that do not match the criteria (<0.708), all items have reached a reliable point. Construct reliability was calculated using Cronbach Alpha and Composite reliability (CR) yielded greater than (>0.7) and AVE exceeded the acceptable value (>0.5) and thus the questionnaire items fulfilled and ensured the reliability of the instrument. The results of the construct reliability check based on discriminant validity can be done by looking at the AVE value to show the size of the indicator variance contained by the construct. Discriminant validity criteria refer to where the AVE value limit is 0.5. The results show that all AVE values for are (>0.5). In addition, the value of the square root of the AVE indicates a high discriminant validity value and can be accepted because the AVE square root value of all variable constructs is above the correlation value between the other construct values.